A Novel Neurorehabilitation Approach for Neural Plasticity Overstimulation and Reorganization in Patients with Neurological Disorders - Alashram, Anas R.; Annino, Giuseppe (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2023)
Neurological disorders are those that are associated with impairments in the nervous system. These impairments affect the patient’s activities of daily living. Recently, many advanced modalities have been used in the rehabilitation field to treat various neurological impairments. However, many of these modalities are available only in clinics, and some are expensive. Most patients with neurological disorders have difficulty reaching clinics. This review was designed to establish a new neurorehabilitation approach based on the scientific way to improve patients’ functional recovery following neurological disorders in clinics or at home. The human brain is a network, an intricate, integrated system that coordinates operations among billions of units. In fact, grey matter contains most of the neuronal cell bodies. It includes the brain and the spinal cord areas involved in muscle control, sensory perception, memory, emotions, decision-making, and self-control. Consequently, patients’ functional ability results from complex interactions among various brain and spinal cord areas and neuromuscular systems. While white matter fibers connect numerous brain areas, stimulating or improving non-motor symptoms, such as motivation, cognitive, and sensory symptoms besides motor symptoms may enhance functional recovery in patients with neurological disorders. The basic principles of the current treatment approach are established based on brain connectivity. Using motor, sensory, motivation, and cognitive (MSMC) interventions during rehabilitation may promote neural plasticity and maximize functional recovery in patients with neurological disorders. Experimental studies are strongly needed to verify our theories and hypothesis.
Keywords: Neural plasticity; Motor rehabilitation; Neurological disorders; Therapy; Recovery.